Anxiety and Depression Trajectories in Young Adults Up to 5 Years After Being Diagnosed With Cancer - Lars Sjödin; Sarah Marklund; Claudia Lampic; Lena Wettergren (Cancer Medicine)
ABSTRACT Aims This study aimed to identify and characterize trajectories of anxiety and depression symptoms in a national cohort of young women and men up to 5 years after being diagnosed with cancer. Furthermore, potential sociodemographic, clinical, and psychosocial factors predictive of different trajectory groups were examined. Methods A population‐based sample of 1010 young adults aged 18–39 at diagnosis with selected cancers/tumors (brain/breast/cervical/lymphoma/ovarian/testicular) completed a survey 1.5 years, 3 years (T2, n = 722) and 5 years (T3, n = 659) post‐diagnosis. Responses to the Hospital Anxiety and Depression Scale were computed using five trajectories as outcome groups: Stable cases, Stable non‐cases, Improving, Worsening, and Fluctuating. Multinomial logistic regression models were performed to identify predictive factors of different trajectories. Results The most common trajectories for anxiety symptoms were Stable non‐cases (36%) and Stable cases (26%), followed by Improving (17%), Fluctuating (11%), and Worsening (10%). In contrast, the dominant trajectory for depression symptoms was Stable non‐cases (69%), with smaller groups identified as Improving (10%), Worsening (8%), Stable cases (7%), and Fluctuating (6%). Factors associated with several unfavorable trajectories were female sex, pre‐diagnosis support for emotional issues, fatigue, and financial problems (p < 0.05). Conclusion Symptoms of anxiety and depression follow five different developmental paths among young people with cancer. Within the first 5 years after a cancer diagnosis, a majority of young adults meet clinical levels of anxiety (64%) and a third meet clinical levels of depression (31%). It is important to consider risk factors for mental illness in the follow‐up care of people with cancer.